2001
DOI: 10.2337/diabetes.50.10.2301
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Antilipolysis Restores Insulin Sensitivity During Growth Hormone Exposure

Abstract: Stimulation of lipolysis and the induction of resistance to insulin's actions on glucose metabolism are wellrecognized effects of growth hormone (GH). To evaluate whether these two features are causally linked, we studied the impact of pharmacologically induced antilipolysis in seven GH-deficient patients (mean [؎ SE] age 37 ؎ 4 years). Each subject was studied under four different conditions: during continuation of GH replacement alone (A), after discontinuation of GH replacement for 2 days (B), after GH repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
88
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 41 publications
13
88
1
Order By: Relevance
“…Some (11,28) but not all (9,10,27) studies have shown that GH might have a direct effect on EGP. It is well established that elevation of plasma FFA concentrations by Intralipid can stimulate EGP (29,31,32) and it has been suggested that the inhibitory effect of FFA on suppression of EGP by insulin is more due to its effect on glycogenolysis than on gluconeogenesis (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some (11,28) but not all (9,10,27) studies have shown that GH might have a direct effect on EGP. It is well established that elevation of plasma FFA concentrations by Intralipid can stimulate EGP (29,31,32) and it has been suggested that the inhibitory effect of FFA on suppression of EGP by insulin is more due to its effect on glycogenolysis than on gluconeogenesis (32).…”
Section: Discussionmentioning
confidence: 99%
“…There is ample evidence that chronic GH replacement therapy in GHD patients induces insulin resistance by concomitant activation of lipolysis and that this untoward effect on glucose metabolism can be prevented by prior inhibition of lipolysis by acipimox (9,10). To dissect the effects of GH on lipolysis and glucose metabolism from other secondary effects we studied the metabolic effects of GH in previously GH-untreated patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevation of plasma GH levels also results in increased plasma insulin levels and insulin resistance (6). The increased insulin secretion can be explained by a direct effect of GH on the pancreatic ␤-cells (33,40), whereas the insulin resistance may be explained by increased fatty acid oxidation in some (34), but not all, situations (18,37).…”
mentioning
confidence: 99%
“…2001), which may in part be mediated by an increase in adipose lipolysis and circulating FFAs (Nielsen et al. 2001). Initial studies with ghrelin in humans attempted to control for ghrelin's secondary GH release, using either infusion of somatostatin to inhibit GH release, or GH‐deficient participants (Gauna et al.…”
Section: Discussionmentioning
confidence: 99%